2020
DOI: 10.1021/jacs.0c10415
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Intermolecular Radical C–H Amination

Abstract: Radical reactions hold a number of inherent advantages in organic synthesis that may potentially impact the planning and practice for construction of organic molecules. However, the control of enantioselectivity in radical processes remains one of the longstanding challenges. While significant advances have recently been achieved in intramolecular radical reactions, the governing of asymmetric induction in intermolecular radical reactions still poses challenging issues. We herein report a catalytic approach th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 74 publications
1
45
0
Order By: Relevance
“…Functional groups such as alkyl (4), cyano (8), alkyloxy (13), and trifluoromethyl (7 and 11) are tolerated, as are halides (5, 6, 9, and 10) that can be used subsequently in well-developed cross-coupling reactions. The diene substrates with a terminal C-C triple bond (17), a disubstituted phenyl group (14, 15, and 16), a thienyl group (18), a naphthyl group (19 and 20), and a pyrenyl group (21) can provide the corresponding products with a er value as high as 95:5. A screening of the alkyl diacyl peroxides revealed that not only primary alkyl radicals but secondary alkyl radicals can participate (33) are tolerated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional groups such as alkyl (4), cyano (8), alkyloxy (13), and trifluoromethyl (7 and 11) are tolerated, as are halides (5, 6, 9, and 10) that can be used subsequently in well-developed cross-coupling reactions. The diene substrates with a terminal C-C triple bond (17), a disubstituted phenyl group (14, 15, and 16), a thienyl group (18), a naphthyl group (19 and 20), and a pyrenyl group (21) can provide the corresponding products with a er value as high as 95:5. A screening of the alkyl diacyl peroxides revealed that not only primary alkyl radicals but secondary alkyl radicals can participate (33) are tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…The two faces of a planar radical or the two invertomers of pyramidal radicals must be recognized and the radical must be rapidly converted into the desired products before undesirable side reactions can take place. Recently, the creation of stereoselective C-C, C-N, C-Br bonds on a radical center has been incrementally realized by Fu [1][2][3][4][5] , Liu [6][7][8][9] , Ready 10 , Reisman 11,12 , and others [13][14][15][16][17][18][19][20] (Fig. 1a), and these breakthroughs have inspired the field, leading to significant progress and discovery of many relevant and useful reactions.…”
mentioning
confidence: 99%
“…The mild oxidant N ‐fluoroalkylamide ( N‐F‐1 ) resulted in a dramatically decreased yield of 3 . The much stronger oxidant NFSI [6, 7b–d] gave only a trace amount of the desired product, likely as a result of the polymerization of 2 a induced by the attack of the less bulky imidyl radical on the terminal alkyne (Figures S1–S3). Collectively, these observations suggest that a suitable oxidant capable of abstracting a C(sp 3 )−H bond efficiently as well as tolerating a terminal alkyne is of great importance for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Chiral amidoporphyrin ligands have enabled impressive enantioselective aminations, including the first intermolecular example in 2020 ( Scheme 3 B). 55 In the same year, Chang extended the concept to intramolecular amidation for the preparation of γ-lactams from dioxazolones ( Scheme 3 C). 56 The PcFe system is remarkable for its high activity, activating even primary alkyl C–H bonds at a catalyst loading of just 0.5 mol % (TON was 47 000 for benzylic C–H bonds).…”
Section: Next Generation Metal Catalystsmentioning
confidence: 99%